DESIGNING A CASPER SURVEY TOOL OPTIMIZED FOR RILEY COUNTY - Kumar, Ganesh (My University, 2021)
The Community Assessment for Public Health Emergency Response is an epidemiological tool developed by the Centers for Disease Control and Prevention to provide household-based information regarding a community in an easy, quick, and cost-effective way. It has become a very effective tool in conducting a form of Rapid Needs Assessment in both emergency and non-emergency situations. This project involved developing a process to optimize the CASPER tool to make it suitable for use in Riley County, Kansas. My primary focus involved developing optimal cluster and household sampling methodologies for this process. The development of the sampling methodologies for Riley County, closely mirrored the process outlined in the CASPER toolkit provided by the CDC. Once our team had the process formalized, a CASPER trial-run was conducted in Riley County on four pre-selected clusters. Our experience involving the logistics of carrying out the trial-run, helped to further refine the process and add recommendations which may be useful to those who may conduct the survey in the future.
Keywords: CASPER; Sampling; Cluster; Trial-run; Riley County Kansas